Preliminary Blood Pressure Screening in a Representative Sample of Extremely Obese Kuwaiti Adolescents - Rima Abdul Razzak; Asma Elmteri; Taiba Elkanderi; Fareedah Ishaq; Munera Eljasem; Saja AlDuraie; Jenan Al-Boloushi; Fatma Elbanay; Latifa Eldabos (Journal of Obesity)
A relationship between blood pressure (BP) and obesity has been found in young adults, but no data are available for adolescents in Kuwait. 257 adolescent (11–19 years) participants were categorized into two groups according to their BMI; 48 nonobese (21 males: 43.7% and 27 females: 56.3%) with mean age of years and 209 obese (128 males: 61.25% and 81 females: 38.75%) with mean age of years. The mean BMI was  kg/m2 for the nonobese group and  kg/m3 for the obese group. Most BP measures based on a single screening were significantly higher in the obese group. The prevalence of elevated BP was significantly higher in the obese subjects (nonobese: 13%; obese: 63%; ). In the obese group, there was a significant positive correlation between total sample BMI and all BP measures except the pulse pressure. There was a similar rate of elevated blood pressure between males and females (64% versus 60%; ). For both isolated systolic elevated BP and isolated diastolic elevated BP, the prevalences were comparable between the males (systolic: 42%; diastolic: 5%) and females (systolic: 34%; diastolic: 14%). Only systolic BP was positively correlated with BMI in obese adolescent males (Spearman ; ), with a significant correlation between BMI with diastolic (Spearman ; ) and mean BP (Spearman ; ) in females.